2011
DOI: 10.1148/radiol.11110537
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Stenoses: Accuracy of 64–Detector Row CT Angiography in Segments with Mild, Moderate, or Severe Calcification—A Subanalysis of the CORE-64 Trial

Abstract: Purpose:To evaluate the infl uence of cross-sectional arc calcifi cation on the diagnostic accuracy of computed tomography (CT) angiography compared with conventional coronary angiography for the detection of obstructive coronary artery disease (CAD). Materials and Methods:Institutional Review Board approval and written informed consent were obtained from all centers and participants for this HIPAA-compliant study. Overall, 4511 segments from 371 symptomatic patients (279 men, 92 women; median age, 61 years [i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 25 publications
4
82
0
3
Order By: Relevance
“…Low diagnostic specificity and PPV of CCTA in calcified plaques is mainly due to high false positive rates caused by blooming artifacts which result from heavy calcification in the coronary arteries. [11][12][13][14][15] This is a widely known limitation of CCTA. Some recent studies have addressed this issue by showing the improved diagnostic performance of CCTA with use of bifurcation angle measurement when compared to the conventional approach based on coronary lumen stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low diagnostic specificity and PPV of CCTA in calcified plaques is mainly due to high false positive rates caused by blooming artifacts which result from heavy calcification in the coronary arteries. [11][12][13][14][15] This is a widely known limitation of CCTA. Some recent studies have addressed this issue by showing the improved diagnostic performance of CCTA with use of bifurcation angle measurement when compared to the conventional approach based on coronary lumen stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] It is well known that high calcification or high calcium score in the coronary arteries results in false positive results, thus leading to low specificity and positive predictive value (PPV). [11][12][13][14][15] This limitation has been addressed to some extent with use of image processing methods as reported in some studies. [16][17][18] Another approach to improve diagnostic value of CCTA in the diagnosis of calcified plaques is to use left coronary bifurcation angle as opposed to the conventional method of measuring coronary lumen stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Количественные измерения при перфузионной МРТ сердца демонстрируют хоро-шую корреляцию с измерениями ФРК [138]. Исполь-зование высокомощных магнитов при 3,0 Т, хотя они пациента посегментная оценка кальциноза оказывает более сильное влияние на диагностическую точность, чем общее содержание кальция [159], причем влия-ние кальция на точность КТА коронарных артерий менее выражено при меньших значениях ЧСС и при использовании современных КТ-систем [160,161]. В случае, если индекс коронарного кальция не опре-делялся и кальциноз наблюдается только по заверше-нии КТ-ангиографического сканирования, может быть благоразумным воздержаться от количествен-ной оценки стеноза в областях распространенного кальциноза и признать результаты исследования "неясными" (рис.…”
Section: стресс-мрт сердцаunclassified
“…When the calcification is severe, there can be an exaggerated appearance once the contrast fills the lumen. In the analysis of the study named CorE-64, Vavere et al (22) demonstrated that the diagnostic quality decreased in cases with multiple coronary artery calcifications. In our study, especially in distal segments and in cases identified to have severe calcifications, MSCT identified different rates of obstruction compared to CCA.…”
Section: Discussionmentioning
confidence: 99%